STUDI HIGIENE DAN SANITASI MAKANAN DI TEMPAT PENGELOLAAN MAKANAN (TPM) DI KECAMATAN CINERE, DEPOK TAHUN 2020 - Sulkifly Ibrahim (2020)
Food hygiene and sanitation is an effort to control food elements, individuals, locations and needs that can cause disease as well as health side effects. The purpose of this study was to describe food hygiene and sanitation at the Food Management Place in Cinere District, Depok City in 2020. The design was research study is quantitative descriptive. The population was study was the A2 food handlers and restaurants in the Cinere District, Depok City. A totaling 110 participants (food handlers and food stalls/restaurants) were recruited as samples by using a simple random sampling technique. Data were analyzed by using a univariate analysis. The analysis results show that food place sanitation condition (62.7%), environmental sanitation facilities (70.9%), education (53.6%), service period (71.8%) and knowledge (74.5%) were in accordance with the standard. However, behavior were found to be poor (58.2%,). So overall, the handlers and restaurants have met hygiene and sanitation standards. For the restaurant manager is to equip the windows and doors with insect repellent equipment, separating the hand washing container which is still integrated with the other washing container, and completing the trash bin with the closed one